Women Victims of Intimate Partner Violence in Shelters: Correlates of Length of Stay and Subsequent Reentries. (October 2019) - Fernández-González, Liria; Calvete, Esther; Borrajo, Erika
The purpose of this study was to examine which variables are associated with the length of stay at a shelter and the likelihood of reentering the shelter after a first stay in a sample of 777 women victims of intimate partner violence. The results showed that the women's health, having been previously abused, and having children with them at the shelter were the best set of correlates for length of shelter stay; lack of social support, having been previously abused, and the abusers' being unemployed increased the risk of repeated use of shelters. The implications for intervention are discussed.